Challenges in family sports tourism development at Pulau Langkawi: perceptions of sports tourists / Khor Poy Hua... [et al.] - Khor, Poy Hua; Mohd Nor, Siti Wardah; Radzuwan, Radzliyana; Othman, Nuraimi; Mohd Kassim, Ahmad Fikri (Universiti Teknologi MARA, Perlis, 2022)
Today, families are considered the main contributors to the growing market of tourism business. This trend is motivated by the growing awareness on retaining family ties and generating memories of family memories. Making decision for family sports tourism is a challenging task, especially when it involves inter-generational tourism. Although family tourism is growing globally, details of challenges that constrain family tourists varies across the globe and surprisingly no study has so far addressed the issue thoroughly especially in Malaysia. This paper relates the challenges experienced by families of different income levels in family sports tourism at Pulau Langkawi. The objectives were answered based on a survey conducted among 243 family sports tourists at Pulau Langkawi and data collected using questionnaire was statistically tested using MANOVA. Regardless of family income level, quantitative findings identified the influential challenges in significant order as structural constraints, interpersonal constraints, and intrapersonal constraints, with participation fee as the main constraint factor. Family sports tourists of different income group were not significantly constrained by any specific barrier. There is a potential of gaining more knowledge on the barriers experienced in family sports tourism by focusing on other demographic variables. This paper generates a better thought on the challenges experienced in family sports tourism and the prospect in the upcoming sports tourism business.